El rescate de los ingas y pallas con la participación de los niños de 2 a 5 años de los CNH y su representación social con la fiesta del cantón Tisaleo - Bastidas Sánchez, María Alejandra (2019)
This research focused on the theme "La Inga Palla (Cult of Santa Lucia) as a social representation of the Tisaleña culture aims to rescue the cultural identity of the children of the canton through the presentation of the Inga Palla and make it declared Cultural Heritage of Humanity. Therefore it was necessary to use a research methodology that allows the application of research types such as descriptive-explanatory, it allows to describe the problem and determine the causes that generate it, for the research process determined the population defined In the parents of the children of 0 a 5 years old CNH "Growing with Our Children", the data was collected through an interview designed to obtain the information for this study, it revealed the current condition of the Inga party. Palla, also established results that showed that the participation of children in the party of the Inga Palla, is limited, however there is a predisposition of parents to participate with their children in the activities of the same, proceeds to discuss the case finding that the new generations are losing that attachment to the party, as well as the children, so they settled down the creation of a cultural day at the CNH "Growing with Our Children", which was attended by children from 0 a 5 years old, and it was concluded that the authorities of Canton Tisaleo and the teachers of the CNH provided the necessary support for the application of this project and thus its objectives were met KEYWORDS: SOCIAL REPRESENTATION, INGA PALLA, CULTURAL IDENTITY, INTEGRATION, FESTIVITIES